2013
DOI: 10.1002/cbdv.201200271
|View full text |Cite
|
Sign up to set email alerts
|

Variability of n‐Alkanes and Nonacosan‐10‐ol in Natural Populations of Picea omorika

Abstract: This is the first report of population variability of the contents of n-alkanes and nonacosan-10-ol in the needle epicuticular waxes of Serbian spruce (Picea omorika). The hexane extracts of needle samples originated from three natural populations in Serbia (Vranjak, Zmajevački potok, and Mileševka Canyon) were investigated by GC and GC/MS analyses. The amount of nonacosan-10-ol varied individually from 50.05 to 74.42% (65.74% in average), but the differences between the three investigated populations were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The statistical analyses show a high intrapopulation variability which is congruent with both molecular and phytochemical data [8,12,[28][29][30]. The lowest variability was found in the population VRA, where all except one individual are grouped close to each other.…”
Section: Discussionsupporting
confidence: 73%
“…The statistical analyses show a high intrapopulation variability which is congruent with both molecular and phytochemical data [8,12,[28][29][30]. The lowest variability was found in the population VRA, where all except one individual are grouped close to each other.…”
Section: Discussionsupporting
confidence: 73%
“…C 29 , C 25 , C 27 , and C 23 have been found to be dominant in P. peuce Griseb . and C 23 , C 27 , C 25 in P. heldreichii Christ . However, if the composition of P. nigra needle waxes at the population level in this study was compared, there was an observable domination of first two n ‐alkanes (C 27 and C 25 ) in all populations of subsp.…”
Section: Resultsmentioning
confidence: 62%
“…Among the compounds constituting the cuticular waxes, n ‐alkanes have been used extensively as chemotaxonomic markers in different plant families . Furthermore, many authors suggested n ‐alkanes as very informative markers in the studies of geographic variation and/or identification of infraspecific taxa of Pinus , Picea , and Juniperus species. In the case of P. nigra , variability and differentiation of native populations using n ‐alkane markers have already been studied, but in a relatively reduced part of its natural range .…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly encountered are homologous series of even-numbered fatty acids, primary alcohols, alkyl esters and aldehydes, as well as odd-numbered alkanes, secondary alcohols and ketones (Kunst and Samuels 2003). In addition, detail population investigations based on the composition of secondary alcohol nonacosan-10-ol of the needle waxes of P. halepensis (Matas et al 2003), P. heldreichii (Nikolić et al 2012a), P. peuce (Nikolić et al 2012b) and Picea omorika (Nikolić et al 2013a) in different parts of their distribution were reported recently.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was already known that CPIs and ACLs could be use as chemotaxonomic markers (Herbin and Robins 1968), in environmental studies (Lockheart et al 1998), in paleoenvironmental reconstructions (Corrigan et al 1978), etc. Furthermore, a number of studies suggested n-alkanes as very informative markers in the studies of geographic variation and/or identification of infraspecific taxa of Pinus (Nikolić et al 2010(Nikolić et al , 2012a2012b;Mitić et al 2018a;, Picea (Nikolić et al 2013a), Juniperus (Dodd and Poveda 2003;Rajčević et al 2013), and other species (Günthardt -Goerg 1986). Furthermore, chemotaxonomic implications between several conifers were reported, too (Nikolić et al 2013b.…”
Section: Accepted Manuscriptmentioning
confidence: 99%